The Advanced Smart Grid : Edge Power Driving Sustainability. - Carvallo, Andres (Artech House, 2015)
Placing emphasis on practical ""how-to"" guidance, this cutting-edge resource provides a first-hand, insider's perspective on the advent and evolution of smart grids in the 21st century. This book presents engineers, researchers, and students with the building blocks that comprise basic smart grids, including power plant, transmission substation, distribution, and meter automation. Moreover, this forward-looking volume explores the next step of this technology's evolution. It provides a detailed explanation of how an advanced smart grid incorporates demand response with smart appliances and ma